QTL analysis of field resistance to Xanthomonas axonopodis pv. manihotis in cassava - Jorge, V.; Fregene, Martin A.; Velez, C.M.; Duque E., Myriam Cristina; Tohme, Joseph M.; Verdier, Valerie M. (Springer, 2001)
We evaluated cassava bacterial blight (CBB) infection in an pair-cross population of 150 individuals derived from an intra-specific cross between two non-inbred cassava (Manihot esculenta Crantz) lines. The replicated trials were carried out in the field under high disease pressure over two consecutive crop cycles. Evaluations were conducted at 4 and 7 months after planting for the two cycles. Simple regression analysis and the nonparametric Kruskal-Wallis rank-sum test revealed that eight quantitative trait loci (QTLs) were involved in resistance. We detected changes in QTLs from crop cycle to crop cycle. The pathogen population (Xanthomonas axonopodis pv. manihotis) was also monitored over the period, using a restriction fragment length polymorphism probe and pathogenic tests. Changes in QTL detection over the 2 years could be correlated with changes in pathogen population structure. One QTL, located in linkage group D, was conserved over the two crop cycles, and in field to greenhouse evaluations. This study thus identified molecular markers useful for marker assisted-selection, a technique that can accelerate the long, multiple-season process of breeding for CBB resistance.